Entrepreneurship challenges: A case study among single mother entrepreneurs in northern region - Abu, Noor Hidayah; Zainal Abidin, Faudziah; Ahmad Zaidi, Mohamad Faizal; Mansor, Mohd Fitri (School of Technology Management and Logistics (STML), 2019)
Entrepreneurship is not a foreign concept for women. Today, the number of women who enter the entrepreneurial field has been shown to increase tremendously. For example, McKay (2001) reported that in 1999 almost half of the small businesses in the United States were owned by women. In the meantime Shafizad, Coetzer, & Alan (2016) stated that women play a major role in the growth of small businesses in Australia. In addition, the UK Government also estimated that nearly a quarter and a third of business firms in the country were owned by women (Brierley, 2014). Meanwhile, Orhan and Scott (2001) reported that 26% of total entrepreneurs in France were women. Meanwhile closer to home, the ex-Minister of Women, Family, and Community Development, Datuk Seri Rohani Abdul Karim, had stated that in Malaysia, 19.7% of Small and Medium-sized Enterprises (SMEs) are owned by women. From that percentage, about 91.7% are involved in the service sector, followed by 6.9% in the manufacturing sector, and the rest are in other sectors (Jaafar & Sazili, 2017). However, it was reported that there are at least 1.9% single mothers who have their own business enterprises in Malaysia.